N-2 Polyphenol Targets Vascular Calcium Channels to Exert Antihypertensive Effects: In Vitro and In Vivo Evaluation - Khasanov, Alikhon; Abdullaev, Izzatullo; Kadirova, Shokhida; Mamajanov, Muxtorjon; Zaynabiddinov, Anvar; Omonturdiev, Sirojiddin; Makhmudov, Lazizbek; Inomjonov, Dolimjon; Gayibov, Ulugbek; Esanov, Rakhmat; Matchanov, Alimjan (Trends in Sciences, 2025)
This study investigated the antihypertensive potential of the natural compound N-2 polyphenol using both in vitro and in vivo approaches. In vitro assays focused on its effects on vascular smooth muscle cells, particularly voltage-dependent L-type calcium channels, receptor-operated calcium channels, and endothelium-mediated pathways. N-2 significantly inhibited Ca2+ influx through L-type channels, producing 86.2 ± 2.4% relaxation at 50 μM (IC5₀ = 30 μM), and suppressed receptor-operated channel-mediated contractions by 90.5 ± 3.5% at 45 μM. Endothelium-dependent vasorelaxation was partially mediated by nitric oxide (NO), as shown using the NOS inhibitor L-NAME (100 μM). In endothelium-denuded preparations, N-2 still reduced contractility by 38.0 ± 3.1%, suggesting partial NO-cGMP-PKG pathway involvement. In vivo, an adrenaline-induced hypertension model in rats showed that intravenous N-2 markedly lowered blood pressure. Three h after administration, systolic and diastolic pressures dropped to 74.7 ± 3.3 and 62.7 ± 4.1 mmHg, respectively. These results demonstrate that N-2 polyphenol exerts strong antihypertensive effects through both calcium channel blockade and endothelium-dependent mechanisms. Its dual mode of action highlights N-2 as a promising candidate for managing hypertension. HIGHLIGHTS N-2 polyphenol induced strong vasorelaxation in rat aortic rings. It inhibited L-type and receptor-operated Ca²⁺ channels effectively. Endothelium-dependent relaxation involved the NO–cGMP–PKG pathway. In vivo, N-2 lowered blood pressure in adrenaline-induced hypertension. N-2 is a promising natural antihypertensive candidate compound. GRAPHICAL ABSTRACT